The marketing system of the dried fish industry in Roxas City - Villanueva-Baria, Mary Ann
Dried fish has been one of the prominent industries in the Philippines. The country's geographical location is very strategic and convenient for fish processors. However, the marketing system of dried fish industry varies in different areas, depending on the locale of the dried fish industry. In line with this, the researcher came up with this study to describe specifically the marketing system of the dried fish industry in Roxas City and determine the factors affecting its pricing mechanism. Thirty-one male processors, twenty-one female processors and traders were chosen to give light to this study. There were five purposely chosen barangays. The locales of the study are the barnagays Dumulog, Baybay, Cogon, Barra and Olotayan. These barangays were chosen according to the availability of dried fish processing in the area. To come up with relevant data regarding the marketing system of the dried fish industry in Roxas City, interview schedules were conducted, computation of percentages, mean and frequency count were done. Internet and Library Research were also employed in data gathering. Secondary data from the local government of Roxas City also helped upon coming up with this descriptive study. Roxas City, being surrounded largely by water, is indeed a good venue for fish processing. It has large-scale dried fish processing that supplies if not all, but most of the provinces in the country. This industry followed the same marketing system as with the other products do. The marketing system employed in the dried fish industry is from processors to traders to the consumers. Traders, as usual, act as middlemen that bridge the product from the processors to the consumers. These traders have the greatest control over the pricing mechanism of the dried fish. Other than the traders, the pricing mechanism of the dried fish can also be affected by weather conditions and availability of the raw materials. The law of supply and demand also guides the marketing system of the dried fish industry in Roxas City. The most common type of marketing in the dried fish industry in Roxas City is wholesale. The concentration of the processors is towards the traders, since they have a permanent market with them. Traders maintain a suki relationship with the consumers as well as the processors to them for consistent profit. The dried fish industry in Roxas City is very large. It has a very large market since 86% of its dried fish are shipped out of Roxas to Manila and other provinces and only a meager 14% goes to Banica Market. The study concludes that, though the dried fish industry in Roxas City follows a simple marketing system, yet this industry is very competitive and promising.